Front St., Dawson, Yukon Territory, June 1898. - Hegg, Eric A., 1867-1948 (1898)
Shows dogteam hauling cart in street, "Jo's Juneau Restaurant" on right. Caption on image: "Front Street Dawson June '99". Klondike Gold Rush.